Return-to-work for people living with long COVID: A scoping review of interventions and recommendations - Gagan Nagra; Victor E. Ezeugwu; Geoff P. Bostick; Erin Branton; Liz Dennett; Kevin Drake; Quentin Durand-Moreau; Christine Guptill; Mark Hall; Chester Ho; Pam Hung; Aiza Khan; et al. (PLoS ONE, 2025)
Introduction Long COVID is characterized by the presence of new onset or persistent symptoms 3 months after a suspected or confirmed history of SARS-CoV-2 infection. It is a complex and multi-faceted condition that affects people in different ways. Long COVID affects individuals’ labour market participation. While some cannot work, others may return to work (RTW) in a limited capacity. Determining what rehabilitation or related strategies are safe and effective for facilitating RTW is necessary. Objectives To synthesize evidence on RTW interventions for people living with Long COVID and to identify ‘promising’ interventions for enhancing work ability and RTW. Methods We followed Arksey & O’Malley’s methodology and the PRISMA extension for scoping reviews. Five electronic bibliographic databases and grey literature were searched. The literature search included various study designs, such as randomized controlled trials (RCT), quasi-experimental designs, and observational studies as well as clinical practice guidelines (CPGs). Two reviewers conducted screening and data extraction, with disagreements resolved through consensus. Intervention studies were categorized as promising (statistically significant RTW outcomes or ≥ 50% RTW), somewhat promising (20% to < 50% RTW), not promising (non-statistically significant RTW outcomes or < 20% RTW), or uncertain (did not specify proportion of RTW). Results Twelve CPGs and nineteen intervention studies were identified. Of the intervention studies, 5 were cohort studies, 3 quasi-experimental studies, 4 observational, 2 interventional, 3 RCTs, and 2 case reports. Promising interventions included multimodal and interdisciplinary work-focused rehabilitation, multidisciplinary inpatient and outpatient rehabilitation, psychoeducation, pacing, and breathing strategies, shifting focus from symptom monitoring to optimizing functional outcomes, enhanced external counterpulsation inflatable pressure to improve blood flow, and constraint-induced cognitive therapy. Conclusion Many uncertainties remain regarding which RTW interventions are effective or the optimal characteristics of these interventions.